The Making of Europe - Conventional or Unconventional? The Convention as an Alternative Method of Drafting European Treaties - Lucie Königová; Petr Kratochvíl (Czech Journal of International Relations, 2005)
This article presents a critical analysis of the Convention method, which was used to draft the founding treaties underpinning European integration. The article examines the nature, advantages, and disadvantages of the Convention method, comparing it with the traditional Intergovernmental Conference (IGC) method. After identifying the general features of the Convention and the IGC, we compare the behaviour of four small EU Member States (Belgium, Ireland, the Czech Republic, and Estonia) at the Convention on the Future of the European Union. Following this, we focus on the elements of socialization and rational bargaining manifest in the four countries' behaviour. Finally, we show how aspects of intergovernmental diplomacy and parliamentary procedures are mixed in the Convention model, and how certain aspects of deliberative democracy mingle with rational choice bargaining.